1993
DOI: 10.1093/ajh/6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Monitoring in Normotensive and Hypertensive Type 2 Diabetics Prevalence of Impaired Diurnal Blood Pressure Patterns

Abstract: To assess the prevalence of an impaired diurnal blood pressure (BP) pattern in a population of both normotensive and hypertensive diabetics, noninvasive ambulatory BP monitoring (SpaceLabs 5200, Redmond, WA) was performed in 96 outpatients with type 2 diabetes (47 normotensives and 48 hypertensives) and in 103 control subjects without diabetes (50 normotensives and 53 hypertensives). Mean 24 h and daytime (06:00 to 22:00) BP and heart rate (HR) were not statistically different in diabetic patients compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
2
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 0 publications
3
58
2
2
Order By: Relevance
“…In particular, Verdecchia et al 23,24,38 showed an increase of the cardiovascular events in 'non-dipper' patients, and Shimada et al 39 found higher incidence of cerebrovascular injury, as documented by magnetic resonance (MRI), and finally Palatini et al 40 detected a higher incidence of left ventricular hypertrophy in non-dipper hypertensive subjects. In particular, in patients with diabetes and patients with chronic renal failure, 41 in whom a more important global cardiovascular risk for all daytime BP level is well known, a lack or a reduction in nocturnal pressure fall was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Verdecchia et al 23,24,38 showed an increase of the cardiovascular events in 'non-dipper' patients, and Shimada et al 39 found higher incidence of cerebrovascular injury, as documented by magnetic resonance (MRI), and finally Palatini et al 40 detected a higher incidence of left ventricular hypertrophy in non-dipper hypertensive subjects. In particular, in patients with diabetes and patients with chronic renal failure, 41 in whom a more important global cardiovascular risk for all daytime BP level is well known, a lack or a reduction in nocturnal pressure fall was observed.…”
Section: Discussionmentioning
confidence: 99%
“…16,18 Our results suggest that white coat hypertension may represent the first stage in the development of hypertension. Two participants died during the follow-up, and no conclusion can be drawn from the mortality.…”
Section: Discussionmentioning
confidence: 66%
“…Of the hypertensive type 2 diabetic subjects, 8-23% have white coat hypertension 16 and 30-31% show the non-dipper phenomenon. 18 The 24-h ABPM could be useful in the treatment of hypertension of subjects with type 2 diabetes to detect the ones with white coat hypertension (lowrisk) and the non-dipper phenomenon (high-risk).…”
Section: Introductionmentioning
confidence: 99%
“…Fogari and cols. compared 47 normotensive and 48 hypertensive diabetic patients with 103 healthy individuals and were unable to detect a decrease in NBP in 30% of the normotensive diabetics and in 31% of hypertensive patients (18). Bauduceau and cols.…”
Section: Discussionmentioning
confidence: 92%